Propagação in vitro de Cattleya trianaei (Linden & Reichenbach fil.) (Orchidaceae) em meios de culturas e com doses de fertilizante comercial - Galdiano Junior, Renato Fernandes [UNESP]; Mantovani, Cibele [UNESP]; Macedo Lemos, Eliana Gertrudes de [UNESP] (My University, 2012)
The use of culture media produced with commercial fertilizers can represent a simple and low cost alternative for commercial orchid propagation. The aim of this study was to evaluate the in vitro growth of plantlets of Cattleya trianaei in culture medium MS reduced and and formulated with Peters® NPK 10-30-20 in different doses. 90 day-old plantlets with two leaflets were submitted to five treatments (T1 - reduced MS; T2 - Peters® 1 g L -1; T3 - Peters® 2 g L-1; T4 - Peters® 3 g L -1 and T5 - Peters® 5 g L-1) arranged in a completely randomized design with five replicates with 25 plantlets for each treatment and incubated during 180 days, with subcultures at each 60 days, when the number of roots, root length, number of leaves, shoot length and shoot fresh matter were evaluated. The simplified culture medium with fertilizer Peters® 3 g L -1 presented results statistically different as for the number of roots, number of leaves, shoot length and shoot fresh matter and it can be recommended for in vitro growth of this ornamental orchid.
In vitro propagation of Cattleya trianaei (Linden & Reichenbach fil.) (Orchidaceae) in culture media under commercial fertilizer concentrations
Keywords: Micropropagation; Orchid; Simplified culture medium; Cattleya trianaei; Orchidaceae